PENERAPAN MODEL JIGSAW DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS ARGUMENTASI PADA SISWA SMA - Aini, Nuraini; Harahap, Eddy Pahar; Bambang, Siti Enik Mukhoiyaroh (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effectiveness of the Jigsaw cooperative learning model in improving the argumentative writing skills of Phase F A2 students at SMA Negeri 5 Kota Jambi. The study was motivated by students’ low ability to formulate thesis statements, construct logical arguments, and apply appropriate linguistic features. This research employed Classroom Action Research (CAR) with a mixed-method approach conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 35 students, and data were collected through observation, writing tests, interviews, and documentation. The findings revealed that classical learning mastery in Cycle I reached 45.7% and increased to 97,1% in Cycle II after instructional improvements were implemented through intensive guidance and the use of student worksheets (LKPD). In addition, students’ participation and self-confidence in the learning process also improved. These findings indicate that the Jigsaw model is effective in enhancing argumentative writing skills while promoting collaborative and student-centered learning.